Debates on the measurement of global poverty - Anand, Sudhir, 1946-; Segal, Paul, 1977-; Stiglitz, Joseph E. (Oxford : Oxford University Press, 2010)
This volume brings together the most recent debates in the measurement of global poverty - a topic of the greatest importance if we are to develop effective strategies for poverty reduction and have any real sense of whether progress is being made towards the achievement of the Millennium Development Goals.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poverty